Investigation of seafood mislabeling in Asia: a review of the literature and mitigation strategies - Thinh Dinh Do; Li Lian Wong (Journal of Agriculture and Food Research)
Seafood is among the most traded food commodities globally because of consumer preferences for healthy and diverse protein sources. The seafood market is expected to further grow in the future to meet the strong commercial demand. With its crowded population and dynamic economy, Asia plays a critical role in the global seafood market. Asia accounts for approximately two-thirds of seafood consumption globally. Increased consumption and lax regulations on product labeling have led to seafood mislabeling, which has serious consequences for both consumers and natural resources. However, the status of seafood mislabeling in Asian countries remains largely unknown because of the limited number of studies. In addition, the data accumulated on the continent need to be summarized to provide a foundation for future studies and management, especially in countries where seafood mislabeling has not been investigated. The present review summarizes the status of seafood mislabeling based on scientifically published investigations on the continent and proposes relevant mitigation strategies. The examination revealed that all published papers reported the occurrence of seafood mislabeling in Asia. The mislabeling rate highly varied among the countries, types of products, and scales of investigation. Seafood mislabeling can result in economic losses for consumers, harm their health, and damage natural resources. The present review will significantly contribute to our understanding of seafood fraud in Asia. Therefore, the findings from this study could serve as fundamentals for implementing seafood management more effectively in the region.